2019
DOI: 10.1111/evo.13671
|View full text |Cite
|
Sign up to set email alerts
|

In love and war: The morphometric and phylogenetic basis of ornamentation, and the evolution of male display behavior, in the livebearer genus Poecilia

Abstract: Exaggerated male traits under sexual selection are often used for both competition and courtship, raising the question of whether ornaments evolved simultaneously for both functions, or if use in one context preceded use in another. Here, we apply a phylogenetic approach to study the evolution of ornamental dorsal fins in male poeciliid fish of the subgenera Mollienesia and Limia, which exhibit convergent development of an enlarged dorsal fin, and often direct erect‐fin displays to male and female conspecifics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 116 publications
(298 reference statements)
0
33
1
Order By: Relevance
“…In guppies, males also have these two mating strategies, and Pilastro and Bisazza (1999) showed that courting males delivered three times higher numbers of sperm to the females than the sneaky ones, which significantly increased their probability of insemination. This could also be the case in Poecilia gillii, as males show different mating strategies with large and colorful dominant males guarding a harem of females and continuously chasing away competitors, whereas small and dull males mimic females in appearance and sneak mate when the opportunity presents itself (Goldberg et al, 2019;Furness, Hagmayer and Pollux, unpublished data).…”
Section: Pre-copulatory Mechanismsmentioning
confidence: 98%
See 2 more Smart Citations
“…In guppies, males also have these two mating strategies, and Pilastro and Bisazza (1999) showed that courting males delivered three times higher numbers of sperm to the females than the sneaky ones, which significantly increased their probability of insemination. This could also be the case in Poecilia gillii, as males show different mating strategies with large and colorful dominant males guarding a harem of females and continuously chasing away competitors, whereas small and dull males mimic females in appearance and sneak mate when the opportunity presents itself (Goldberg et al, 2019;Furness, Hagmayer and Pollux, unpublished data).…”
Section: Pre-copulatory Mechanismsmentioning
confidence: 98%
“…In mating systems that include sexual harassment, larger females may be better than small females at avoiding unwanted sexual copulation attempts; i.e., earlier studies have shown that larger females are more likely to swim away from approaching males by moving to deeper and faster flowing water to avoid sexual harassment by males (Brewster and Houde, 2003;Croft et al, 2006;Magellan and Magurran, 2006). Laboratory and field observations have shown that Poecilia gillii lacks courtship behavior and relies solely on coercive mating, with males relentlessly chasing females and females continuously fending of obtrusive and unwanted suitors (Ptacek, 2005;Goldberg et al, 2019;Furness, Hagmayer and Pollux, unpublished data). Female poeciliid fish seem to avoid these coercive mating attempts in two ways: by chasing away males or by moving to a habitat with a lower density of males (Croft et al, 2006;Magellan and Magurran, 2006;Magurran, 2011).…”
Section: Effect Of Female Traits On Multiple Paternitymentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of muscle tissue from the caudal peduncle were taken from Limia species from Cuba, Hispaniola, and Jamaica. We used four to five individuals per species, except in cases where sampling was limited ( (27,43,54). We use P. dominicensis (44), P.…”
Section: Samplingmentioning
confidence: 99%
“…Nested within the species native to Hispaniola are L. vittata and L. caymanensis (2,53) which are the only species native to their respective islands, Cuba and Grand Cayman (27,43). While these general patterns are maintained in the few phylogenies of Limia, most of these analyses use only a few species (51,52,54). The most robust species sampling and reliable phylogeny to date used nine species of Limia, among them only two native to Lake Miragoâne, Limia nigrofasciata and Limia islai, formerly known as "Tiger Limia" (2,43,45).…”
Section: Introductionmentioning
confidence: 99%